Association Among Fear of Falling, Stress, and Quality of Life in Adults and Older People - Chuangchai, Warawoot (Journal of Architectural/Planning Research and Studies (JARS), 2017)
Fall-related injuries in older people have become a crucial and unease topic in public health area. The present study investigated the relationship of fall-related factors among fear of falling (FOF), stress, and quality of life (QOL) in adults and older people via structured questionnaires and informal interviews. A cross-sectional study was conducted in the central region of Thailand with 33 participants (9 males, 24 females) aged 45 - 86 years. Significant differences were indentified between groups in psychological well-being (P = 0.021), and stress (P = 0.034), respectively. QOL was significantly correlated with stress (r = -0.551, P = 0.002), and FOF (r = 0.517, P = 0.002), respectively. FOF was significantly correlated with stress (r = -0.310, P = 0.040) as well. The main evidence obtained from the present study suggests that decreasing FOF and/or stress could give prerequisite contribution to improving QOL not only in adults but also in older people. Fall prevention strategies may be more effective if consideration is given to the built environmental design in terms of design for sustainability in order to reduce the incidence possibility, minimize the chance of consequent injuries in elderly Thai population, and enhance their life qualities.